Advanced ultra-light multifunctional metallic-glass wave springs - Panagiotopoulos, Nikolaos T.; Georgarakis, Konstantinos; Jorge Jnr, Alberto Moreira; Aljerf, M.; Botta, Walter José; Greer, A. Lindsay; Yavari, Ahmad (Elsevier, 2020)
We show that, using thermo-elastic processing, metallic-glass foils can be shaped, without being embrittled, into linear and annular wave springs. These springs exhibit an undulatory behaviour, unique to metallic-glass foils, in which under compression the number of arcs in the spring increases, increasing the load-bearing capacity and the spring constant. We evaluate the performance limits of the metallic-glass wave springs, and consider how the undulatory behaviour can be exploited. The metallic-glass springs can operate over the same load-ranges as commercially available crystalline wave springs, but have material volumes (and therefore weights) that are one to two orders of magnitude less. Their energy storage per unit material volume is as high as 2600 kJ m−3. We suggest that the undulatory behaviour is important in rendering the springs fail-safe in case of overload. We discuss the range of applicability of thermo-elastic processing, the likely working limit of metallic-glass wave springs, and the potential for application of metallic-glass springs in MEMS devices.
Keywords: Metallic glasses; Wave springs; Shaping; Elastic behaviour; Embrittlement; Energy storage